Carotid Calcification in Mice: A New Model to Study the Effects of Arterial Stiffness on the Brain. Issue 3 (19th June 2013) - Sadekova, Nataliya; Vallerand, Diane; Guevara, Edgar; Lesage, Frédéric; Girouard, Hélène
Abstract : Background: Arterial stiffness has been identified as an important risk factor for cognitive decline. However, its effects on the brain's health are unknown, and there is no animal model available to study the precise impact of arterial stiffness on the brain. Therefore, the objective of the study was to develop and characterize a new model specific to arterial stiffness in order to study its effects on the brain. Methods and Results: Calcium chloride (CaCl2 ) was applied to carotid arteries of mice, inducing an increase in collagen distribution and intima–media thickness, a fragmentation of elastin, a decrease in arterial compliance and distensibility, and an increase in cerebral blood flow pulsatility (n=3 to 11). Calcium deposits were only present at the site of CaCl2 application, and there was no increase in systemic blood pressure or change in vessel radius making this model specific for arterial stiffness. The effects of carotid stiffness were then assessed in the brain. Carotid calcification induced an increase in the production of cerebral superoxide anion and neurodegeneration, detected with Fluoro‐Jade B staining, in the hippocampus (n=3 to 5), a key region for memory and cognition. Conclusions: A new model of arterial stiffness based on carotid calcification was developed and characterized. This new model meets all the characteristics of arterial stiffness, and its specificity allows the study of the effects of arterial stiffness on the brain.